Pengalaman Ibu Bekerja dalam Pemberian AIS Eksklusif di Lingkungan Universitas Muhammadiyah Magelang - Wijayanti, Kartika; Prawitasari, Shinta; Wenny, Wenny (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2016)
Background: The percentage of breastfeeding within the last 24 hours is decreasing with increasing age of the baby with the percentage 6 month babies is only about 30.2%. The percentage Central Java reached 34.38%, the low, and became the 6th lowest at Indonesia. This is not met with the government’s target of 80% in 2010. In Magelang district, the number is decreased from 45.18% in 2011 and 25.6% in 2012. Total coverage of exclusive breastfeeding at Universitas Muhammadiyah Magelang is 13%.Objective: To identify employment mother’s experience for exclusive breastfeeding at Muhammadiyah Magelang University.Method: This is a qualitative study, transcendental phenomenological approach. The subjects of this study are employment mother at Muhammadiyah Magelang University who have babies 6-36 months. Data was collected with in-depth interviews, observation, and documentation. Sampling was carried out using purposive sampling technique. Data analysis using 6 stages Colaizzi data analysis. This study began in February 2014 - February 2015.Result and Discussion: This study resulted 6 categories: employment mother’s experiences for exclusive breastfeeding at work less fun, supporting factors of exclusive breastfeeding is complex, mother’s knowledge of exclusive breastfeeding is good, physical, technical, and pshycological preparation were necessary to give exclusive breastfeeding, and expectation of the workplace that support for exclusive breastfeeding.Conclusion: Employment mother’s experience for exclusive breastfeeding less fun. Mother’s effort to prepare for exclusive breastfeeding such as knowledge, physical, technical, and pshycological. Mother’s expectation is workplace that supports exclusive breastfeeding.Keywords: Experience, Employment mother, exclusive breastfeeding